The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.17576/gema-2017-1704-11
|View full text |Cite
|
Sign up to set email alerts
|

Penyebaran Dialek Melayu Di Langkawi: Analisis Geolinguistik (The Distribution of Malay Dialects in Langkawi: A Geolinguistic Analysis)

Abstract: ABSTRAKKajian dialek geografi di Malaysia sebelum ini telah memberikan maklumat taburan dialek secara umum berdasarkan perbezaan fonologi dan leksikal. Kajian tersebut telah menjadi asas kepada kajian geolinguistik pada hari ini. Dalam kajian kali ini, varian leksikal "daun kari" dan "daun kesum" dalam dialek Melayu Kedah di Pulau Langkawi telah diteliti. Berasaskan analisis geolinguistik, elemen linguistik telah digabungkan bersama dengan faktor bukan bahasa seperti bentuk muka bumi, persempadanan, migrasi da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Despite her contribution to illustrating the spread of dialect in the state of Pahang, Collins (1989Collins ( , 1999, on the other hand, rejected this method upon adhering to Jalaluddin et al (2017) and Hamzah et al (2014) due to the similar concept of political labelling. Omar (1977), Hussein (1973), and Karim and Ibrahim (1977) divided Pahang into groups based on their phonetic distinctions.…”
Section: Problem Statement and Research Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…Despite her contribution to illustrating the spread of dialect in the state of Pahang, Collins (1989Collins ( , 1999, on the other hand, rejected this method upon adhering to Jalaluddin et al (2017) and Hamzah et al (2014) due to the similar concept of political labelling. Omar (1977), Hussein (1973), and Karim and Ibrahim (1977) divided Pahang into groups based on their phonetic distinctions.…”
Section: Problem Statement and Research Objectivementioning
confidence: 99%
“…Omar (1977), Hussein (1973), and Karim and Ibrahim (1977) divided Pahang into groups based on their phonetic distinctions. However, these studies were impressionistic (Jalaluddin et al, 2017) as they relied on isolated phonological findings and dismissed the comparative linguistics approach. The comparison of interdialectal or subdialect illustrates the linguistic properties in the area.…”
Section: Problem Statement and Research Objectivementioning
confidence: 99%
“…Sometimes they asked for additional time to allow each group member to present their opinion and provide feedback on the opinion of their fellow group members. The increase in the mean score of attitudes for the treatment group in learning Malay grammar after using the Jigsaw II technique is seen as convincing teachers to diversify their strategies to strengthen the student's knowledge and skills in achieving a good level of grammar proficiency (Jalaluddin et al, 2010).…”
Section: Differences In Students' Attitudes Towards Learning Malay Gr...mentioning
confidence: 99%
“…The problem with the attitudes of students in learning Malay is also caused by the teacher's pedagogy (Mahamod, 2011). Jalaluddin et al (2010) found that students became bored and started to lose interest in learning the Malay language due to the same Malay language teaching activities from the primary to secondary level. The study found that almost 20 per cent of the sample male students showed a negative attitude towards the Malay language due to the curriculum being very broad and often changing in grammar.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation